Comparative study on the deterioration of granite under microwave irradiation and resistance-heating treatment (Fracture and Structural Integrity, 2019)
To investigate the deterioration of granite under microwave irradiation and heat transfer, granite specimens were heated up to 400-1000 °C and then kept for 15 min. Uniaxial compressive strength testing results demonstrate a similar variation in two groups in 400-900 °C, which is initial strengthening (less than 500 °C), subsequent weakening (500-600 °C) and final stabilizing (600-900 °C). Furthermore, the specimen irradiated by microwaves presented a second decline at 1000 °C. Compared to heat transfer, microwave irradiation can reduce the strengthening due to localized transition plasticity and further promotes the deterioration of rock structure in weakening stage. TG/DSC results indicate that the strengthening is related to the iron mineral transition. The formation of porous glass substance which is mainly composed of feldspar and biotite. Furthermore, temperature-controlled microwave irradiation induced the variation of feldspar crystallinities, which is consistent with the corresponding UCS data, especially the plagioclase. In practical application, microwaves can be used to irradiate the vulnerable positions (surface edge and cleavage) and kept the whole rock mass around 600 °C.
Keywords: Granite; Thermal damage; Microwave irradiation; Heat transfer